Indonesian Case of Political Identity, Post Truth, and Computational Propaganda - Fajar Cahyono; Kusuma Putri; Hafizh Nurul Faizah (Yayasan Rumah Peneleh, 2019)
The purpose of this study was to determine the use of Computational Propaganda in organizing and manipulating public opinion on social media with the issue of identity politics and its relation to the Post Truth in the Indonesian Presidential Election in 2019. There are two methods used in this study: A) qualitative methods are used to answer how to use Computational Propaganda for political marketing in the 2019 Presidential Election, and B) quantitative methods using Social Network Analysis (SNA) on Twitter's social media platform to determine the use of bots in manipulating opinions public during the presidential election campaign. The results of this study are Computational Propaganda using identity politics in the 2019 Presidential Election.